Novel criteria for the observe-zone of the ESC 0/1h-hs-cTnT algorithm - Lopez-Ayala, Pedro; Nestelberger, Thomas; Boeddinghaus, Jasper; Koechlin, Luca; Ratmann, Paul David; Strebel, Ivo; Gehrke, Juliane; Meier, Severin; Walter, Joan; Rubini Gimenez, Maria; Mutschler, Eugenio; Miró, Òscar; et al. (Circulation, 2021)
Background: - - The non-ST-segment-elevation myocardial infarction (NSTEMI) guidelines of the European Society of Cardiology (ESC) recommend a 3h cardiac troponin determination in patients triaged to the observe-zone of the ESC 0/1h-algorithm; however, no specific cutoff for further triage is endorsed. Recently, a specific cutoff for 0/3h high-sensitivity cardiac troponin T (hs-cTnT) change (7 ng/L) was proposed, warranting external validation. - - Methods: - - Patients presenting with acute chest discomfort to the emergency department were prospectively enrolled into an international multicenter diagnostic study. Final diagnoses were centrally adjudicated by 2 independent cardiologists applying the fourth universal definition of myocardial infarction, on the basis of complete cardiac workup, cardiac imaging, and serial hs-cTnT. Hs-cTnT concentrations were measured at presentation, after 1 hour, and after 3 hours. The objective was to externally validate the proposed cutoff, and if necessary, derive and internally as well as externally validate novel 0/3h-criteria for the observe-zone of the ESC 0/1h-hs-cTnT-algorithm in an independent multicenter cohort. - - Results: - - Among 2076 eligible patients, application of the ESC 0/1h-hs-cTnT-algorithm triaged 1512 patients (72.8%) to either rule out or rule in NSTEMI, leaving 564 patients (27.2%) in the observe-zone (adjudicated NSTEMI prevalence, 120/564 patients, 21.3%). The suggested 0/3h-hs-cTnT-change of <7 ng/L triaged 517 patients (91.7%) toward rule-out, resulting in a sensitivity of 33.3% (95% CI, 25.5-42.2), missing 80 patients with NSTEMI, and ≥7 ng/L triaged 47 patients toward rule-in (8.3%), resulting in a specificity of 98.4% (95% CI, 96.8-99.2). Novel derived 0/3h-criteria for the observe-zone patients ruled out NSTEMI with a 3h hs-cTnT concentration <15 ng/L and a 0/3h-hs-cTnT absolute change <4 ng/L, triaging 138 patients (25%) toward rule-out, resulting in a sensitivity of 99.2% (95% CI, 96.0-99.9), missing 1 patient with NSTEMI. A 0/3h-hs-cTnT absolute change ≥6 ng/L triaged 63 patients (11.2%) toward rule-in, resulting in a specificity of 98% (95% CI, 96.2-98.9) Thereby, the novel 0/3h-criteria reduced the number of patients in the observe zone by 36%s and the number of type 1 myocardial infarction by 50%. Findings were confirmed in both internal and external validation. - - Conclusions: - - A combination of a 3h-hs-cTnT concentration (<15 ng/L) and a 0/3h absolute change (<4 ng/L) is necessary to safely rule out NSTEMI in patients remaining in the observe-zone of the ESC 0/1h-hs-cTnT-algorithm. - - Registration: - - URL: https://clinicaltrials.gov; Unique identifier: NCT00470587.
Gesehen am 09.11.2021